CAPTURE: a multinational, cross-sectional study of cardiovascular disease prevalence in adults with type 2 diabetes across 13 countries - Mosenzon, Ofri; Alguwaihes, Abdullah; Leon, Jose Luis Arenas; Bayram, Fahri; Darmon, Patrice; Davis, Timothy M E; Dieuzeide, Guillermo; Eriksen, Kirsten T; Hong, Tianpei; Kaltoft, Margit S; Lengyel, Csaba; Rhee, Nicolai A; et al. (Cardiovascular diabetology, 2021)
BACKGROUND: There is a paucity of global data on cardiovascular disease (CVD) prevalence in people with type 2 diabetes (T2D). The primary objective of the CAPTURE study was to estimate the prevalence of established CVD and its management in adults with T2D across 13 countries from five continents. Additional objectives were to further characterize the study sample regarding demographics, clinical parameters and medication usage, with particular reference to blood glucose-lowering agents (GLAs: glucagon-like peptide-1 receptor agonists and sodium-glucose co-transporter-2 inhibitors) with demonstrated cardiovascular benefit in randomized intervention trials. METHODS: Data were collected from adults with T2D managed in primary or specialist care in Australia, China, Japan, Czech Republic, France, Hungary, Italy, Argentina, Brazil, Mexico, Israel, Kingdom of Saudi Arabia, and Turkey in 2019, using standardized methodology. CVD prevalence, weighted by diabetes prevalence in each country, was estimated for the overall CAPTURE sample and participating countries. Country-specific odds ratios for CVD prevalence were further adjusted for relevant demographic and clinical parameters. RESULTS: The overall CAPTURE sample included 9823 adults with T2D (n = 4502 from primary care; n = 5321 from specialist care). The overall CAPTURE sample had median (interquartile range) diabetes duration 10.7 years (5.6-17.9 years) and glycated hemoglobin 7.3% (6.6-8.4%) [56 mmol/mol (49-68 mmol/mol)]. Overall weighted CVD and atherosclerotic CVD prevalence estimates were 34.8% (95% confidence interval [CI] 32.7-36.8) and 31.8% (95% CI 29.7-33.8%), respectively. Age, gender, and clinical parameters accounted for some of the between-country variation in CVD prevalence. GLAs with demonstrated cardiovascular benefit were used by 21.9% of participants, which was similar in participants with and without CVD: 21.5% and 22.2%, respectively. CONCLUSIONS: In 2019, approximately one in three adults with T2D in CAPTURE had diagnosed CVD. The low use of GLAs with demonstrated cardiovascular benefit even in participants with established CVD suggested that most were not managed according to contemporary diabetes and cardiology guidelines. Study registration NCT03786406 (registered on December 20, 2018), NCT03811288 (registered on January 18, 2019).
Keywords: Risk Factors; ženské pohlaví; Cardiovascular disease; Protective Factors; lidé; Diabetes Mellitus, Type 2; Non-interventional study; prognóza; hodnocení rizik; Atherosclerotic cardiovascular disease; senioři; Aged; Risk Assessment; prevalence; lidé středního věku; Cardiovascular Diseases; Prevalence; ochranné faktory; Time Factors; Humans; Glucagon-like peptide-1 receptor agonists; Type 2 diabetes; Prognosis; kardiovaskulární nemoci; průřezové studie; hypoglykemika; mužské pohlaví; Cross-Sectional Studies; Hypoglycemic Agents; Male; rizikové faktory; časové faktory; Sodium-glucose co-transporter-2 inhibitors; Middle Aged; diabetes mellitus 2. typu; Female